2014
DOI: 10.1128/jvi.00388-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Small Interfering RNA Screens Reveal VAMP3 as a Novel Host Factor Required for Uukuniemi Virus Late Penetration

Abstract: The Bunyaviridae constitute a large family of enveloped animal viruses, many of which are important emerging pathogens. How bunyaviruses enter and infect mammalian cells remains largely uncharacterized. We used two genome-wide silencing screens with distinct small interfering RNA (siRNA) libraries to investigate host proteins required during infection of human cells by the bunyavirus Uukuniemi virus (UUKV), a late-penetrating virus. Sequence analysis of the libraries revealed that many siRNAs in the screens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Several previous reports demonstrated that the SNARE complex is involved in viral infection (46)(47)(48). Meier et al reported that siRNA-mediated knockdown of the SNARE protein VAMP3 resulted in the inhibition of endocytic intracellular trafficking of a bunyavirus, Uukuniemi virus, indicating that SNARE protein-mediated membrane fusion is needed for the efficient entry of Uukuniemi virus into cells (49). Ad infection was also inhibited by knockdown of SNAP25 at the step of viral entry (Fig.…”
Section: Mir-27 Inhibits Adenovirus Infectionmentioning
confidence: 71%
“…Several previous reports demonstrated that the SNARE complex is involved in viral infection (46)(47)(48). Meier et al reported that siRNA-mediated knockdown of the SNARE protein VAMP3 resulted in the inhibition of endocytic intracellular trafficking of a bunyavirus, Uukuniemi virus, indicating that SNARE protein-mediated membrane fusion is needed for the efficient entry of Uukuniemi virus into cells (49). Ad infection was also inhibited by knockdown of SNAP25 at the step of viral entry (Fig.…”
Section: Mir-27 Inhibits Adenovirus Infectionmentioning
confidence: 71%
“…While a consistently low number of exact genes overlap across related siRNA screens, it is nonetheless clear that similar screens find bioinformatically related genes, e.g., genes that cluster in common pathways and complexes like the nuclear pore complex (NPC) with HIV-1 and the vacuolar ATPase (V-ATPase) for IAV or HRV (Bushman et al, 2009;Hao et al, 2013;Perreira et al, 2015;Stertz & Shaw, 2011;Zhu et al, 2014). With closer study it became readily apparent that this low level of saturation within the dataset of each primary screen was due to a high level of false negatives (Hao et al, 2013;Meier et al, 2014;Zhu et al, 2014). False negatives with RNAi may come about for several reasons including difficulty in targeting a protein (prolonged protein half-life or sufficient remaining catalytic activity), nonspecific toxicity of siRNAs, and plate edge effects.…”
Section: Rnai Screening Problems and Some Solutionsmentioning
confidence: 99%
“…SFV-and VSV-infected cells were fixed at 5 h p.i., and UUKV-infected cells were fixed at 19 h p.i. SFV and VSV infection was detected on the basis of green fluorescent protein (GFP) expression, and UUKV infection was detected by immunostaining, as described previously (48).…”
mentioning
confidence: 99%